DEVELOPMENT OF MATHEMATICS LEARNING TOOLS USING THE HORAY COURSE REVIEW TYPE COOPERATIVE MODEL (CRH) IN MATERIAL COMPOSITION AND INVERSE FUNCTIONS - Nursamilasari; Leo Adhar Effendi (UIR PRESS, 2020)
This study aimed to produce learning tools based on a valid CRH type of cooperative learning model. The learning tools developed are in the form of a Learning Implementation Plan (RPP) and Student Worksheets (LKPD). The development model used in this research is the Plomp model, which is modified into four stages, namely: (1) Initial investigation, (2) Design, (3) Realization/construction, (4) Test, evaluation, and revision. The data analysis technique used is descriptive statistical analysis. From the research results, the average total validation of the RPP is 88.67%, with very valid criteria. This means that the RPP made by the researcher is suitable for use or trial. Then, the average total validation of LKPD is 84.98%, with quite valid criteria. This means that the LKPD made by the researcher is feasible to use but requires a small revision. Based on the results of these studies, it can be concluded that the development of learning tools based on the CRH type cooperative model on the material of compositional and inverse functions whose validity has been tested is feasible to use